2017
DOI: 10.1007/s10802-017-0308-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effect on Recidivism for Juveniles Who Have Sexually Offended: a Multilevel Meta-Analysis

Abstract: The current study investigated the effect on recidivism of treatment aimed at juveniles who have sexually offended. It also assessed the potential moderating effect of type of recidivism, and several treatment, participant and study characteristics. In total, 14 published and unpublished primary studies, making use of a comparison group and reporting on official recidivism rates, were included in a multilevel meta-analysis. This resulted in the use of 77 effect sizes, and 1726 participants. A three-level meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…The assumption of independent effect sizes underlying traditional meta-analytic methods was therefore violated (Hox, 2010;Lipsey & Wilson, 2001). In line with recently conducted meta-analyses, we applied a multilevel approach in both meta-analyses in order to deal with the interdependency of effect sizes (Assink et al, 2015;Cheung, 2014;Houben, Van Den Noortgate, & Kuppens, 2015;Spruit, Assink, van Vugt, van der Put, & Stams, 2016;ter Beek et al, 2018).…”
Section: Calculation and Analysesmentioning
confidence: 99%
“…The assumption of independent effect sizes underlying traditional meta-analytic methods was therefore violated (Hox, 2010;Lipsey & Wilson, 2001). In line with recently conducted meta-analyses, we applied a multilevel approach in both meta-analyses in order to deal with the interdependency of effect sizes (Assink et al, 2015;Cheung, 2014;Houben, Van Den Noortgate, & Kuppens, 2015;Spruit, Assink, van Vugt, van der Put, & Stams, 2016;ter Beek et al, 2018).…”
Section: Calculation and Analysesmentioning
confidence: 99%
“…Treatment types that incorporate these standards are, therefore, generally considered established treatment. Two recent meta-analyses on the effects of treatments for juveniles with harmful sexual behavior showed no moderating effects for type of treatment (Reitzel & Carbonell, 2006;Ter Beek, Kuiper, et al, 2017;Ter Beek, Spruit, et al, 2017), indicating all included types of treatment to be equally effective in reducing sexual as well as nonsexual recidivism.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the effect of treatment for juveniles with harmful sexual behavior use recidivism as their primary outcome measure. Several meta-analyses have shown that the treatment effect on juvenile recidivism reduction is only moderate (Reitzel & Carbonell, 2006;Walker, McGovern, Poey, & Otis, 2004), or even small and non-significant after controlling for possible publication bias (Ter Beek, Spruit, et al, 2017). Notably, sexual recidivism is relatively rare among juveniles with sexually harmful behavior (Caldwell, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Current research data suggests that cognitive-behavioral and multi-systemic approaches are more effective in reducing recidivism for ASOs (Walker et al, 2004;Fanniff and Becker, 2006;Kim et al, 2016;Ter Beek et al, 2018). The cognitivebehavioral therapeutic approach (CBT) is more widely used, and is considered to be a first-line treatment, whether in groups or individually (Bereiter and Mullen, 2012;Kim et al, 2016;ATSA, 2017).…”
Section: Effectiveness Of Treatment and Recidivismmentioning
confidence: 99%
“…In Caldwell's view, at least some of this significant decrease is due to the effectiveness of specialized treatment programs and increased accessibility to these programs. Indeed, the great majority of meta-analyses on this topic have found that ASO who have received specialized treatment of any kind exhibit lower sexual recidivism rates than do those who have not received any treatment (Walker et al, 2004;Reitzel and Carbonell, 2006;Hanson et al, 2009;Schmucker and Lösel, 2015;Ter Beek et al, 2018). For example, in Reitzel and Carbonell's (2006) meta-analysis of nine studies (N = 2,986), the mean sexual recidivism rate after a mean follow-up period of 59 months was 7.37% in ASO who had received specialized treatment (n = 1,655), and 18.93% in ASO who had received no treatment (n = 1,331).…”
Section: Effectiveness Of Treatment and Recidivismmentioning
confidence: 99%